2001
DOI: 10.1046/j.1365-3059.2001.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of phoma lesions on oilseed rape leaves inoculated with ascospores of A‐group or B‐groupLeptosphaeria maculans(stem canker) at different temperatures and wetness durations

Abstract: In controlled-environment experiments, ascospores of both A-group and B-group Leptosphaeria maculans were able to infect leaves of oilseed rape and produce phoma leaf spot lesions at temperatures from 5 to 208C and wetness durations from 8 to 72 h after inoculation. Lesions formed on leaves inoculated with B-group ascospores had few pycnidia and were darker, smaller and less noticable than the larger, pale grey lesions with many pycnidia produced by A-group ascospores. Lesions formed by A-group or B-group L. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 24 publications
3
59
0
1
Order By: Relevance
“…Huang et al (2003) compared the germination and penetration by ascospores of A-group and B-group of L. maculans on winter-type B. napus. Toscano-Underwood et al (2001) reported the development of blackleg lesions on oilseed rape leaves inoculated with ascospores of A-group and B-group. Hammond and Lewis (1987) used inoculations with single ascospores and with pycnidiospores but did not compare germination and penetration phases of the two spore types.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (2003) compared the germination and penetration by ascospores of A-group and B-group of L. maculans on winter-type B. napus. Toscano-Underwood et al (2001) reported the development of blackleg lesions on oilseed rape leaves inoculated with ascospores of A-group and B-group. Hammond and Lewis (1987) used inoculations with single ascospores and with pycnidiospores but did not compare germination and penetration phases of the two spore types.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is an important parameter for germination of ascospores of L. maculans as well as germ tube elongation on leaf surfaces and for the formation of leaf lesions (Toscano-Underwood et al, 2001;Huang et al, 2003). In controlled-environment experiments performed with increasing temperature from 5°C to 20°C, optimal temperatures of 15-20°C were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Germtubes from ascospores penetrate the leaf through stomata and wounds (Huang et al 2003b). The first symptoms of infection are phoma leaf lesions in the autumn; L. maculans produces pale grey lesions with many pycnidia whilst lesions produced by L. biglobosa are smaller, have a dark margin with a light brown centre and contain few, if any, pycnidia (Brun et al 1997;Biddulph et al 1999;Toscano-Underwood et al 2001). Both L. maculans and L. biglobosa spread asymptomatically from the leaf lamina along tissues of the petiole to the stem Fitt et al 2006b;Huang et al 2006).…”
Section: Introductionmentioning
confidence: 99%